Contagious herding and endogenous network formation in financial networks - Co-Pierre Georg (Deutsche Bundesbank, 2014)
When banks choose similar investment strategies, the financial system becomes vulnerable to common shocks. Banks decide about their investment strategy ex-ante based on a private belief about the state of the world and a social belief formed from observing the actions of peers. When the social belief is strong and the financial network is fragmented, banks follow their peers and their investment strategies synchronize. This effect is stronger for less informative private signals. For endogenously formed interbank networks, however, less informative signals lead to higher network density and less synchronization. It is shown that the former effect dominates the latter.
Keywords: G21; C73; D53; D85; 330; social learning; endogenous financial networks; multi-agent simulations; systemic risk